The simple approach to determination of active diffused phosphorus density in silicon - Sasani, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The diffusion of Phosphorus in silicon using a POCl₃ source has been considered. In the base of Fair-Tsai model of P-diffusion an empirical equation for calculation of active diffused phosphorus density (Qel), is proposed. In this equation, a relationship between (Qel), diffusion time, temperature and junction depth of P-diffused layer (Xj), is presented. The value of sheet resistance (Rs), which is taken from theoretical determination at 900°C, has a good agreement with experimental result.